PENGARUH GAJI, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION KARYAWAN DI PT PEMBANGUNAN JAYA - Sigit Kodrattriana (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
This study aims to analyze the influence of salary, job satisfaction, organizational commitment to Intention at PT. Pembangunan Jaya. The research population is employees of PT. Pembanguna Jaya and the sampling method used Slovin formula which produces 80 respondents to be examined by questionnaire. Salary is an important element that can affect employee performance because it is used to meet various employee needs. Salary is divided into four dimensions, namely salary level (pay level), compensation (benefit) salary increase (pay raise), structure and payroll administration (pay structure and administration). Job satisfaction is a positive feeling about someone's work from a characteristic evaluation. Job satisfaction is divided into job satisfaction towards work (work ef self), pay (pay), promotion opportunities (supervisor) and supervisors (co. workers). Organizational commitment is the extent to which employees take sides with the organization to maintain it. Organizational commitment is divided into three continence commitments, effective commitment and normative commitment. Turnover Intention is an employee's tendency or intention to stop working from his job. Turnover is divided into three dimensions based on intentions (intention to quit), information seeking activities (job search) and thinking of going out (thinking of quit). In this study salary levels of job satisfaction and organizational commitment have a positive effect.